FAKTOR YANG MEMPENGARUHI PARTISIPASI IBU KADER POSYANDU DI KELURAHAN SIDOMULYO TIMUR KOTA PEKANBARU - Veny Veronika Silaban; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to find out the participation and factors that affect the participation of posyandu cadre mothers in Sidomulyo Village of Pekanbaru City. The method used is to use survey methods with quantitative analysis techniques. As for the formulation of the problem in this study (1) How is the form of participation of posyandu cadre mothers in Sidomulyo Village East pekanbaru city? (2) What factors affect the participation of posyandu cadre mothers in Sidomulyo Village East pekanbaru city? The data collection techniques in this study are observations, questionnaires, and documentation. The study was conducted in 16 posyandu located in East Sidomulyo Village with a cadre of 58 people using census technicalities. The data analysis technique in this study is quantitatively descriptive using SPSS version 23. The results of the study explained the form of participation of posyandu cadre mothers, namely energy with indicators of 5 statements classified as high,, material participation forms with 3 statements classified as high and forms of idea participation with 3 statements are in the high category and the factors that influence the participation of posyandu caders are education and knowledge factors. Factors that do not affect the work factors, income factors and length of stay factor. Keywords: Factors, Participation, Posyandu caders